1999
DOI: 10.3923/pjbs.1999.1405.1407
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability Analysis in Linseed (Linum usitatissimum L.)

Abstract: The breeding values of six linseed genotypes viz; LS-1, Chandni, LS-53, LS-62, LS-13 and P-250 were determined in a half diallel experiment using combining ability analysis for seed yield arid five components of seed yield. Significant General Combining Ability (GCA) effects and Specific Combining Ability (SCA) effects were noted for all traits. LS-53, Chandni and IS-1 displayed positive GCA effects for seed yield per plant. LS-53 and Chandni also showed desirable GCA effect for number of branches per plant an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
2
2
0
Order By: Relevance
“…The maximum significant and positive SCA effect was observed by Dipika × RLC 133 (0.42) in E 1 , Gaurav × KB 9610 (0.43) in E 2 , Gaurav × KB 9610 (0.35) in E 3 , Indira × IPI 10 (0.50) in E 4 and Dipika × RLC 133 and Shekhar × RLC 133 (0.31) in PEVs for number of seeds per capsules. Similar finding to the one found for above trait have also been reported by Khan et al [15], Srivastava et al [7], Ratnaparkhi et al [14], Bhateria et al [17], Mishra et al [9] and Mahawar et al [12].…”
Section: Number Of Capsules Per Plantsupporting
confidence: 90%
See 1 more Smart Citation
“…The maximum significant and positive SCA effect was observed by Dipika × RLC 133 (0.42) in E 1 , Gaurav × KB 9610 (0.43) in E 2 , Gaurav × KB 9610 (0.35) in E 3 , Indira × IPI 10 (0.50) in E 4 and Dipika × RLC 133 and Shekhar × RLC 133 (0.31) in PEVs for number of seeds per capsules. Similar finding to the one found for above trait have also been reported by Khan et al [15], Srivastava et al [7], Ratnaparkhi et al [14], Bhateria et al [17], Mishra et al [9] and Mahawar et al [12].…”
Section: Number Of Capsules Per Plantsupporting
confidence: 90%
“…Likewise, highest, significant and positive SCA effect was observed 3.90 (K 29 × GS 384) in E 1 , 2.75 (RLC 133 × IPI 10) in E 2 , 6.08 (KB 9610 × ILS 264 and H 45 × Kartika) in E 3 , 5.54 (ILS 264 × RLC 133 in E 4 and 3.58 (H 45 × Kartika) in PEVs and were considered as poor specific combiners (Table6b). The results were in correspondence to the findings of Khan et al[15], Kumar et al[16], Ratnaparkhi et al[14], Singh et al[8], Mohammadi et al[13], Mishra et al[9] and Mahawar et al[12].…”
supporting
confidence: 91%
“…On the other side, El-Farouk et al (1998) showed that the higher magnitude of variance due to general combining ability for straw yield, plant tallness and technical stem length was predominantly influenced by additive gene effects. Khan et al (1999) reported that the ratio of GCA/SCA effects obtained were higher than unity for seed yield per plant and plant height, while were less than unity for number of capsules per plant, number of seeds per capsule, and 1000-seed weight. Therefore, additive genetic variance was more important for seed yield per plant and plant height, whereas non-additive for others.…”
Section: Analysis Of Combining Ability Variancesmentioning
confidence: 95%
“…In this regard, El-Farouk et al (1998) establish that the mean squares of variances due to general and specific combining ability were significant for straw yield, plant height and technical stem length. Khan et al (1999), Popescu et al (1999), Mohammadi et al (2010), Abdel-Moneam (2014), Pali and Mehta (2014), Amein (2016), Kumar et al (2016), Singh et al (2016), Kumar et al (2017) and Nirala et al (2018) found that both general and specific combining ability variances were significant for all or some seed yield and its components in flax. On the other side, El-Farouk et al (1998) showed that the higher magnitude of variance due to general combining ability for straw yield, plant tallness and technical stem length was predominantly influenced by additive gene effects.…”
Section: Analysis Of Combining Ability Variancesmentioning
confidence: 99%
“…pieces of different texts exist in a text. In short, postmodernism mainly focuses upon "fragmentation, amalgamation of various genres, and text is taken as a positive attribute of language" (M. M. Khan & Akbar, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%